Comparison of Lower Limb Arterial Pulsatility and Ankle Brachial Indices (PI and ABI) in Diabetic Subjects with and Without Neuropathy (BIRDEM Medical Journal, 2012)
Objectives: This study was performed to find out the extent and nature of arterial flow abnormality in diabetic patients with peripheral neuropathy compared to diabetic patients without neuropathy, using duplex colour Doppler technique. Materials and method: This cross sectional study was performed on diabetic subjects in the Department of Radiology and Imaging, BIRDEM from July 2008 to May 2009. Patients were referred from Department of neurology and preventive foot care OPD, BIRDEM, for colour Doppler imaging of lower limb arteries. Total 88 consecutive diabetic patients were included in this study. Out of them 48 were diagnosed cases of diabetic neuropathy (group I) and 40 were diabetic without neuropathy (Group II). In all patients the Ankle Brachial Index (ABI) and Pulsatility Index (PI) were recorded on both left and right lower limb arteries, by using duplex colour Doppler technique. Total no. of patients were 88. 48 had neuropathy. They were 27-57 yrs of age. Result: Unpairedt test was used to find out relationship between the variables.P value